الانتربولوجياالعربية،معضلةالوجود،وجدليةالتبعيةوالتأصيلالمحلي - رحاب, مختار (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
Despite the noveltyArabanthropology  as TributaryGnostic in intellectualcontextsdealingwithhumanbeingswithin the Arab world geography, crystallizedits existence on the basis of descriptive article for nation'sdiscovered cultures, stillAnthropologyArabmakeitsownhistory, and aspires to positioning on the map of the social sciences in the momentum of tugging and rippleshaunted, either suspicion the feasibility of its existence, claimingoscillatingbetweenscientificprosecutors and otherfueled arguments simplistic flat-thought and vision, or to interferewithother relevant social science, or a dilemma of methodthatembodies the generalframework of anthropologic concept built on the basis of (dimension and Strangeness). Under these disparate visions and proposals and discordant willwork in our intervention to try to track the pathsconstituteanthropology in the Arab world as a specialtyknowledge-based, focusing on the stages of resettlementwithinsomeArabuniversities, highlighting the most important researchpreoccupations, and how to takeadvantage of thesefledglingexperiments, willalsowork on the spunyarnoutlook for thisspecializationscientificcontextswithin the Arab world in the social and cultural dimension.